2015
DOI: 10.1098/rspb.2015.1270
|View full text |Cite
|
Sign up to set email alerts
|

Costs of CRISPR-Cas-mediated resistance inStreptococcus thermophilus

Abstract: CRISPR-Cas is a form of adaptive sequence-specific immunity in microbes. This system offers unique opportunities for the study of coevolution between bacteria and their viral pathogens, bacteriophages. A full understanding of the coevolutionary dynamics of CRISPR-Cas requires knowing the magnitude of the cost of resisting infection. Here, using the gram-positive bacterium Streptococcus thermophilus and its associated virulent phage 2972, a well-established model system harbouring at least two type II functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
133
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(148 citation statements)
references
References 68 publications
4
133
0
Order By: Relevance
“…We and others have previously shown that the CRISPR-Cas adaptive immune system of bacteria is associated with an induced cost of resistance [10,13]. This was observed both in P. aeruginosa strain UCBPP-PA14 and in Streptococcus thermophilus strain DGCC7710 [10,13], although in the latter species a constitutive cost of carrying the system was also detected [13].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…We and others have previously shown that the CRISPR-Cas adaptive immune system of bacteria is associated with an induced cost of resistance [10,13]. This was observed both in P. aeruginosa strain UCBPP-PA14 and in Streptococcus thermophilus strain DGCC7710 [10,13], although in the latter species a constitutive cost of carrying the system was also detected [13].…”
Section: Discussionmentioning
confidence: 91%
“…We and others have previously shown that the CRISPR-Cas adaptive immune system of bacteria is associated with an induced cost of resistance [10,13]. This was observed both in P. aeruginosa strain UCBPP-PA14 and in Streptococcus thermophilus strain DGCC7710 [10,13], although in the latter species a constitutive cost of carrying the system was also detected [13]. The induced cost of CRISPR may be because of toxic effects from increased Cas protein production, including autoimmunity [36][37][38], or because of phage-induced damage to the host before the phage is destroyed, or both.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Streptococcus thermophilus, Cas9 is constitutively produced and it confers a fitness cost that is most pronounced during lag phase and at low cell density, when the risk of phage infection is low (7,13,19). Experiments show that CRISPR-Cas-mediated autoimmunity results in deleterious effects, ranging from genome rearrangements and cell filamentation to suicide (9).…”
Section: Significancementioning
confidence: 99%
“…Expression of CRISPR-Cas adaptive immune systems is costly (7,8), possibly because of autoimmunity (9,10) and deployment of resources that could otherwise be invested in growth. To limit fitness costs, some CRISPR-Cas systems are induced upon infection (11)(12)(13).…”
mentioning
confidence: 99%